V˙O2max and the kinetics of V˙O2, muscle oxygen delivery, and muscle deoxygenation - Marinari, Gabriele; DeLorey, Darren S. (Frontiers in Physiology, 2025)
IntroductionAerobic fitness and oxygen uptake kinetics (τV˙O2) at the onset of exercise appear to be inversely correlated, however, the mechanisms underlying changes in τV˙O2 across different levels of aerobic fitness have not been elucidated. The purpose of this study was to investigate the relationship between maximal V˙O2 (V˙O2max) and τV˙O2 and determine whether the capacity to deliver or to utilize O2 limits τV˙O2 in an aerobic fitness dependent manner.MethodsTwenty-three healthy, young males (25 ± 4 years) with a V˙O2max classified as superior (S; V˙O2max > 60 mL·kg−1·min−1, n = 7), good (G; V˙O2max = 45-55 mL·kg−1·min−1, n = 8) or poor (P; V˙O2max < 40 mL·kg−1·min−1, n = 8) performed two moderate-intensity knee-extension (KE) exercise transitions (80% of gas exchange threshold) on a custom-built KE ergometer. V˙O2 was measured breath-by-breath. Leg blood flow (BF) was measured by doppler ultrasound at the femoral artery, and leg vascular conductance (LVC) was calculated as BF·mean arterial pressure (MAP)−1. Near-infrared spectroscopy derived-[HHb] was measured on the vastus lateralis muscle. τV˙O2, τLVC, and τ[HHb] data were averaged and fit with a mono-exponential function.ResultsτV˙O2 was faster in the S (P < 0.01) and G (P < 0.05) fitness groups compared with the P fitness group. τ[HHb] was faster in the S (P < 0.05) compared with the P fitness group. V˙O2max was inversely correlated to τV˙O2 (r = −0.71; P < 0.001) and τ[HHb] (r = −0.55; P < 0.01), but not with τLVC (r = −0.12; P > 0.05). τV˙O2 was positively correlated with τ[HHb] (r = -0.57; P < 0.01), but not with τLVC (r = −0.25; P > 0.05).ConclusionV˙O2max and τV˙O2 were inversely correlated across fitness levels. These findings indicate that O2 delivery is not rate-limiting for τV˙O2 across fitness levels and suggest that the intracellular capacity to utilize O2 may be the primary limiting factor for τV˙O2 in healthy young adults, regardless of aerobic fitness.